2015
DOI: 10.4049/jimmunol.1500531
|View full text |Cite
|
Sign up to set email alerts
|

Spred1, a Suppressor of the Ras–ERK Pathway, Negatively Regulates Expansion and Function of Group 2 Innate Lymphoid Cells

Abstract: Cytokines from group 2 innate lymphoid cells (ILC2s) have been implicated in acute allergic responses, such as papain-induced lung inflammation. However, the means of homeostatic regulation of ILC2s have not been established. In this study, we demonstrated that Spred1, a negative regulator of the Ras–ERK pathway, plays an important role in the proliferation and apoptosis of ILC2s and in cytokine secretion from ILC2s. Intranasal administration of papain stimulated IL-5 and IL-13 production in the lung, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…26 Therefore the lack of IFNAR1 receptor expression might account for the inability of lung ILC2s to respond to type I interferons in the absence of IFN-g in vivo but not in vitro. Mechanistically, IFN-g did not inhibit phosphorylation of p38 and extracellular signal-regulated kinase, both of which have been shown to play prominent roles in ILC2 proliferation and cytokine production, 57,58 but increased the Socs1 mRNA level in a STAT1-dependent manner. A previous study has shown that knockdown of Socs1 enhanced mRNA and protein expression levels of IL-13 and IL-5 in ILC2s, suggesting a limiting role for this protein.…”
Section: Discussionmentioning
confidence: 84%
“…26 Therefore the lack of IFNAR1 receptor expression might account for the inability of lung ILC2s to respond to type I interferons in the absence of IFN-g in vivo but not in vitro. Mechanistically, IFN-g did not inhibit phosphorylation of p38 and extracellular signal-regulated kinase, both of which have been shown to play prominent roles in ILC2 proliferation and cytokine production, 57,58 but increased the Socs1 mRNA level in a STAT1-dependent manner. A previous study has shown that knockdown of Socs1 enhanced mRNA and protein expression levels of IL-13 and IL-5 in ILC2s, suggesting a limiting role for this protein.…”
Section: Discussionmentioning
confidence: 84%
“…Our results showed that the Ras-MEK-ERK pathway plays a major role in TGF-β-mediated upregulation of ST2 in ILC2p and CHILP cells. The Ras-MEK-ERK pathway has recently been demonstrated to play an important role in the maintenance and function of ILC2s 53 . Although the detailed molecular mechanisms underlying TGF-β-mediated-regulation of ST2 remain to be elucidated, our data suggest that this might not rely on the GATA3.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout mice for IL-7Ra or the common γ chain cytokine receptor lack mature ILC2s 61 indicating an important role for IL-7 in generating ILC2s in vivo. Both IL-2 and IL-7 have also been reported to help maintain ILC2 survival 13,61 while culture in combination of IL-2 and IL-7 has been used to maintain ILC2s isolated from lung or Lin −ve ILC progenitors from bone marrow 62,63 . Mesenteric fat ILC2s maintained a Lin −ve /CD45 +ve / Sca1 +ve /KLRG1 +ve phenotype characteristic of ILC2s during culture.…”
Section: Discussionmentioning
confidence: 99%